2004
DOI: 10.1017/s0033291703001508
|View full text |Cite
|
Sign up to set email alerts
|

Cluster analysis of key diagnostic variables from two independent samples of eating-disorder patients: evidence for a consistent pattern

Abstract: Results suggest that patients presenting to eating-disorder services in different countries have clinical features that fall into very similar patterns. These patterns resemble, but are not identical to, existing diagnostic categories.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
26
0
1

Year Published

2006
2006
2011
2011

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 27 publications
(31 citation statements)
references
References 30 publications
4
26
0
1
Order By: Relevance
“…Reasons for the stronger prediction in AN could be greater homogeneity and greater stability over time in AN, both in terms of (non) migration to other diagnoses and lower remission rates. [34][35][36] This suggests strong maintaining factors, and our results indicate that generalized self-control may be one of them. Also, restrictive symptoms relate more to self-image in AN, i.e., symptoms are more ego-syntonic than in other ED groups and therefore less likely to change.…”
Section: Summary Of Results and Methodological Considerationssupporting
confidence: 52%
“…Reasons for the stronger prediction in AN could be greater homogeneity and greater stability over time in AN, both in terms of (non) migration to other diagnoses and lower remission rates. [34][35][36] This suggests strong maintaining factors, and our results indicate that generalized self-control may be one of them. Also, restrictive symptoms relate more to self-image in AN, i.e., symptoms are more ego-syntonic than in other ED groups and therefore less likely to change.…”
Section: Summary Of Results and Methodological Considerationssupporting
confidence: 52%
“…On the other hand, several authors argue that there is solid empirical evidence supporting the notion that AN should be considered a distinct and separate phenotype (Birmingham, Touyz, & Harbottle, 2009;Bulik et al, 2007;Clinton, Button, Norring, & Palmer, 2004;Collier & Treasure, 2004;van Son et al, 2010). The differentiation between AN and other eating disorders is based upon recent evidence including genetics, epidemiology, response to psychotropic drugs and neuroimaging (for a review, see for example Birmingham et al, 2009.…”
Section: Classification Of Anorexia Nervosamentioning
confidence: 99%
“…Following the logic of a transdiagnostic approach a cluster analytic strategy is then appropriate. Using this strategy several cross-sectional studies [32][33][34][35][36][37][38][39] have revealed different subgroups, which resemble, but are not identical to existing diagnostic categories. Most follow-up studies describe the course and outcome of ED in terms of average mean group scores.…”
Section: Introductionmentioning
confidence: 99%